Improving the Peri-operative care of Patients by instituting a 'Block Room' for Regional Anaesthesia. Issue 1 (2nd May 2014) - Chazapis, Maria; Kaur, Navkiran; Kamming, Damon
Abstract: Regional anaesthesia has multiple known benefits over general anaesthesia alone, but requires time and expertise for its application. This study aimed to decrease anaesthetic time and increase total surgical operative time by instituting a 'block room' where regional anaesthesia nerve blocks could be provided by expert anaesthetists in regular scheduled sessions. A baseline audit showed that 2 hours per day was spent on performing nerve blocks. Development of the block room allowed nerve blocks to be performed in parallel to surgical operations, reducing the mean anaesthetic control time from 44 mins to 27 mins. This freed time for an extra operative case per day. In addition, pooling of expertise to one site has allowed excellent teaching opportunities for anaesthetic trainees, and a specific training programme for regional anaesthesia is being produced. In conclusion, instituting a block room has improved the efficiency of our theatre complex, and improved the service deliverable to our patients.